Letters of Indemnity Without Bills of Lading as an Instrument for Carrier Liability Release in Maritime Transportation - Jubaidi, Didi; Wagiman (Ilomata International Journal of Social Science, 2024)
Sea transportation documents, especially bills of lading, play an important role in regulating the rights and oblig ations of the parties involved. A bill of lading is not only a proof of delivery, but also serves as a contractual instrument, proof of ownership, and a basis for dispute resolution. In addition to bills of lading, there is also a letter of indemnity document which has become a growing issue in the world of sea transportation. This document is used as a guarantee by the shipper to the carrier to replace the bill of lading in certain situations, such as speeding up the delivery of goods or resolving administrative issues more efficiently. However, the use of letters of indemnity also poses various legal challenges and risks that need to be considered by all parties involved. This research aims to analyze the position of the issuance of a letter of indemnity without the submission of a bill of lading and evaluate the Indonesian legal perspective on the practice in sea transportation. The research method used is normative juridical, with reference to legal literature and related legal documents. The results show that the issuance of a letter of indemnity without the submission of a bill of lading can lead to various significant problems, especially related to legal uncertainty. This uncertainty includes aspects of the ownership rights of the goods, the responsibility of the carrier, and the potential for misuse of documents that can harm all parties involved.